Meio ambiente como temática para o aprendizado de reações estequiométricas - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This study was proposed based on the difficulties that students have in learning the content of Chemical Reactions Stoichiometry, as well as the causes that make these difficulties so common and recurring. Based on the above, this work has as a major concern to take to the students in a more receptive way, the content of stoichiometry as something more plausible to be understood, with a view to a daily theme. Thus, it is proposed to make a connection between the content of Stoichiometry of Chemical Reactions with the theme Environment, with the purpose of improving the learning of the students involved, thus strengthening their understanding. This study aims to address the content of Stoichiometry, from the application of the Atomic Economy concept with a view to understanding and conceiving environmental issues in Chemistry Teaching, using different strategies and resources so that in this way it can provide the student with better conditions so that it can build significant learning related to the proposed theme, understand the importance of the curricular component Chemistry, as well as its relationship with other areas of knowledge and its applications. The Application and Evaluation of Didactic Material stage, in which it was developed with 9 students from the General Chemistry and General Chemistry II curriculum components, both taught at the Federal University of Pampa, Campus Bagé (RS), covering 04 campus courses. The application was executed in a remote classroom, through the Google Meet platform, in which a virtual questionnaire was applied, covering seven essay questions to the students involved for the acceptability of the proposed theme.
Keywords: Ensino de química; Estequiometria de reações; Meio Ambiente; Ensino superior; Chemistry teaching; Reaction’s stoichiometry; Environment; University education; CNPQ::CIENCIAS EXATAS E DA TERRA